The Effectiveness of The Teenagers' Friends Website Educational Media to Improve Teenagers' Knowledge About Free Sex at State Vocational School 8 Pekanbaru - Dewinny Septalia Dale; Intan Maharani; Hamidah Sari Batubara; Andriani (YAYASAN PENDIDIKAN MANDIRA CENDIKIA, 2026)
Premarital sex refers to sexual behavior between two individuals who are not legally married and is frequently found among adolescents due to a lack of knowledge and comprehensive sexual education. A preliminary survey at SMK Negeri 8 Pekanbaru revealed cases of pregnancy outside marriage. Objective: This study aimed to evaluate the effectiveness of a website-based educational medium in improving adolescents’ knowledge about premarital sex at SMK Negeri 8 Pekanbaru. Methods: This study employed a pre- experimental design with a one-group pre-test and post-test approach. A total of 67 tenth- grade students were selected through total sampling. Data were collected using aquestionnaire administered before and after the educational intervention delivered through the